PAIR PROGRAMMING FOR LEARNING PROGRAMMING SUBJECT IN HIGHER EDUCATION: A SYSTEMATIC REVIEW - Ismail, Nor Zalina; Razak, Mohd Rizal (International Journal of Education, Psychology and Counseling, 2024)
This Systematic Literature Review (SLR) investigates the role of pair programming in higher education, focusing on its impact on students' learning outcomes, collaboration, and programming skill development. As programming courses become increasingly complex, the demand for effective teaching methods has led to the growing popularity of collaborative learning techniques, such as pair programming. However, questions remain regarding its scalability, adaptability, and long-term benefits in educational settings. A thorough search of academic publications from 2021 to 2024 was conducted to explore these issues using databases such as Scopus and Web of Science (WoS). The study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, starting with 42 articles, of which 22 met the inclusion criteria for further analysis. Articles were excluded for irrelevance, mismatched titles, lack of empirical data, or unavailability of full texts. The review categorized its findings into three key themes: (1) Remote and distributed Pair Programming (RPP), (2) psychological and social dynamics, and (3) pedagogical approaches and tools. The results suggest pair programming enhances students' learning performance, particularly in introductory programming courses, by improving problem-solving skills and coding proficiency. However, challenges such as unequal participation and student resistance persist. The success of pair programming largely depends on proper implementation and teacher facilitation. While the review indicates that pair programming holds promise as an instructional strategy in higher education, it emphasizes the need for further research to assess its long-term impact and address its implementation challenges.